2004
DOI: 10.1002/chin.200404223
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Construction of a Monotetrahydrofuran‐Ring Library in Annonaceous Acetogenins by Asymmetric Alkynylation and Stereodivergent Tetrahydrofuran‐Ring Formation.

Abstract: Formation. -(KOJIMA, N.; MAEZAKI*, N.; TOMINAGA, H.; ASAI, M.; YANAI, M.; TANAKA*, T.; Chem. Eur. J. 9 (2003) 20, 4980-4990; Grad. Sch. Pharm. Sci., Osaka Univ., Suita, Osaka 565, Japan; Eng.) -Adam 04-223

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Results from model alkynylations reactions [40], showed that optimum yields in the alkynylation step, using standard conditions, was achieved when the O-protecting group (OP 1 ) was a MOM moiety (89%. >94% de).…”
Section: Fig (5)mentioning
confidence: 98%
“…Results from model alkynylations reactions [40], showed that optimum yields in the alkynylation step, using standard conditions, was achieved when the O-protecting group (OP 1 ) was a MOM moiety (89%. >94% de).…”
Section: Fig (5)mentioning
confidence: 98%
“…Compounds 5.1 and 5.4 were prepared from 3.2 and 3.1 , via 4.2 and 4.1 , respectively, in four easy steps, including mesylation, Sharpless asymmetric dihydroxylation with AD-mix-β, Williamson-type etherification and monobenzoylation. Compounds 5.1 and 5.4 were oxidized using Swern reaction, and the resulting aldehydes, 6.1 and 6.4 , were alkynylated with 1-decyne using Carreira’s enantioselective alkynylation to give both threo and erythro products. The alkynylated products were hydrogenated over Pd−C, and the resulting saturated compounds 7.1 a , b and 7.4 a , b were converted to alcohols 8.1 a , b and 8.4 a , b .…”
mentioning
confidence: 99%